2006
DOI: 10.1097/01.qai.0000227791.92203.d5
|View full text |Cite
|
Sign up to set email alerts
|

A Reliable and Inexpensive EasyCD4 Assay for Monitoring HIV-Infected Individuals in Resource-Limited Settings

Abstract: Serial measurements of absolute CD4+ T-lymphocyte counts are required to initiate and gauge response to therapy and monitor disease progression. Hence, there is an urgent need to evaluate the accuracy and validity of low-cost CD4+ T-cell count assays. Tripotassium EDTA blood specimens from HIV-infected individuals were studied using a novel flow cytometric assay (EasyCD4 assay; Guava Technologies, Hayward, CA) in comparison with standard flow cytometry (FACSCount; Becton Dickinson Immunocytometry Systems, San … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 8 publications
4
28
0
Order By: Relevance
“…In addition, absolute bias increases between Guava® and FACSCalibur® from low to higher strata. Our results confirmed previous studies reporting that Guava® is less accurate at CD4 counts above 500 cells/μl [16,20,21,31]. This difference could be caused by the way of separating monocyte and lymphocyte count which share CD4 on cell surface.…”
Section: Technical Performancessupporting
confidence: 82%
See 1 more Smart Citation
“…In addition, absolute bias increases between Guava® and FACSCalibur® from low to higher strata. Our results confirmed previous studies reporting that Guava® is less accurate at CD4 counts above 500 cells/μl [16,20,21,31]. This difference could be caused by the way of separating monocyte and lymphocyte count which share CD4 on cell surface.…”
Section: Technical Performancessupporting
confidence: 82%
“…Many flow cytometers have been tested [16][17][18][19][20][21][22][23][24]. However, some of this first generation has a few limitations: (i) it was not possible to get CD4 percentage which is very important in children monitoring or (ii) the use of FCM software requires good computer skills by the operator.…”
Section: Introductionmentioning
confidence: 99%
“…In developed countries, CD4 þ T-lymphocyte (CD4) quantification is considered an essential tool in the initiation and monitoring of ARV therapy, and can be performed using both automated and manual bead-based methods. The introduction of lowcost, automated flow cytometric CD4 assays has provided a more affordable option for RLS (1,6,(14)(15)(16); however, affordable flow cytometry remains impractical in many RLS (12,15,17), as even the simplest flow cytometers require ongoing instrument support and better infrastructure than is currently offered in these regions (10,12).…”
Section: Introductionmentioning
confidence: 98%
“…More recently, studies in South Africa have suggested that the two-color CD45/CD4 staining combination on single platform can provide excellent precision and reproducibility at considerably less cost (17). Trials evaluating the adoption of single platforms systems have indeed shown improved precision over dual platform systems (13)(14)(15)(16)19), leading to their recommendation (14,18,20) In resource-limited countries, single platform flow cytometric methods that utilize less complex and less technically challenging equipment, some of which can be powered by a car battery or solar panel, are now being employed (21)(22)(23)(24)(25)(26). Many countries in resource-limited settings are now using these affordable flow cytometric devices in their national ART programs as they scale-up provision of ART to all those adults who meet the immunologic criterion of a CD4 cell count of <200 cells/mm 3 .…”
Section: Cd41 T Lymphocytes Enumerationmentioning
confidence: 99%